(3GdfTQGJ GdENHGQjI aj GdaVGFjGJ GdCLfOGJ h GdCWQ (B/s - (3GdcfGfj, eMSf LdhH s; (3GdOLjdjs ((3YeGf (B:s (3OGQ GeLO ddfTQ h GdJhRjY(B;(3OGQ caGAI GdeYQaI ,s, 2021)
(3dYH CNHGQ GdJdaRjhf OhQG cHjQG aj GdJCKjQ Ydi GdLeGgjQ h JTcjd GQGFge h ejhdge h JhLjgge Gdi bVGjG eYjfI h UQa fXQge Yf GNQi HGdGVGaI Gdi Gf GdehGO GdGNHGQjI ef Gge GdehGO GdJj JbOegG GdeMWGJ GdJdaRjhfjI GdeNJdaI h JYO HeKGHI fGaPI jWdY ef NdGdgG GdeTGgOjf h ge aj efGRdge Ydi GdYGde GdcHjQ h fTQI GdGNHGQ GdJdaRjhf ceG jYQagG NHQGA GdGJUGd gj GdYQV GdGNHGQj GdPj jbOe ddeTGgO Ydi TGTI GdJdaRjhf Ydi GdghGA eHGTQI h jYJeO GdYQV GSGSG Ydi GdNHQ h JSYi fTQI GNHGQ GdJdaRjhf Gdi JRhjO LeGgjQ GdeTGgOjf HGdGNHGQ GdOGNdjI h GdNGQLjI GdJj Jgege h Jge HdGOge HUOb h ehVhYjI dGTHGY UaI MH GdGSJWdGY aVdG Yf Gf GdZGdHjI JYO GdJdaRjhf GdhSjdI GdGYdGejI GdGcKQ UObG GdeLGd GdGNHGQj h GNHGQ GdJdaRjhf dOjgG GdbOQI GdJj JfaQO HgG GdGNHGQ aj GLgRI GdGYdGe GdGNQi dGfgG JYQV UhQI GdeLJeY PGJg h djS KeI eG jVGQY GdJdaRjhf aj bOQJg Ydi Gf jchf eQGI JfYcS YdjgG UhQI GdeLJeY h GdMbjbI GdJj jLH Gf fYjgG gj Gf GdfLGM aj GdGNHGQ ShGA cGfJ GdeMWI eJfhYI GdHQGeL Gh eJNUUI gh GdPj jcSH GdeMWI ghjJgG aj GPgGf GdeTGgOjf h jYRR ef UhQJgG h ecGfJgG YfO eJGHYjgG HYO eQGMd h GYhGe ef GdeeGQSI GdegfjI GdQGbjI h GdeUOGbjI GdYGdjI h GdGMJQGa GdQajYs
Keywords: (3GdCNHGQs; (3GdEYdGe h GdGJUGds; (3GdCbeGQ GdUfGYjIs